BENTUK DAN FUNGSI SANDUR DI DESA SUKOREJO KECAMATAN PARENGAN KABUPATEN TUBAN - Galuh Haryanti Manunggaling Tyas; Srihadi Srihadi (Institut Seni Indonesia Surakarta, 2020)
Sandur in his show tells about the life of people who have a livelihood as a farmer. The problem in this research is how sandur shows form and how Sandur functions. Based on the object studied, this research uses qualitative method. To discuss the form using the concept of Sal Murgiyanto and I Made Bandem which discuss elements of traditional theater which includes dialogue, decorating, dance, accompaniment music, makeup, costumes and dance. Discussing the problem of function using the concept of SD Humardani which belongs to social functions including entertainment functions, educational functions, and solidarity functions. The results showed that Sandur is a folk art in the form of traditional theater. Sandur has 3 innings in the show, namely the opening section, the contents and the closing part. Sandur's performance form can be seen from the elements of the performance consisting of dialogue, decor, costumes, makeup, accompaniment music, singing, and dance. Sandur function is classified into social functions, namely as entertainment, as education, and as community solidarity. Keywords: Sandur, Shape, Function